Application of Islamic Management Ethics in Business Decision Making - Jihan Humairoh (JUMEBIN : Journal of Management, Economics, Business, and Investment, 2025)
This study aims to explore the application of Islamic management ethics in business decision making. In an increasingly complex global context, ethics is becoming an important aspect of running a sustainable and responsible business. Islamic management ethics offers a unique framework, based on the principles of the Qur'an and Sunnah, that can guide business leaders in making fair and transparent decisions. This study uses a qualitative approach with in-depth interviews with Muslim business practitioners and case study analysis of companies that apply Islamic management ethics. The results show that the implementation of Islamic ethical principles, such as fairness, social responsibility, and transparency, not only improves the company's reputation but also creates a positive and productive work environment. Through this research, it is hoped that it can provide new insights into the importance of integrating ethical values in business strategy and encourage companies to consider ethical perspectives in every decision taken. This research also invites academics and practitioners to further explore the relationship between Islamic management ethics and modern business practices, and their impact on the sustainability of companies in the era of globalization.